2008
DOI: 10.1038/leu.2008.326
|View full text |Cite
|
Sign up to set email alerts
|

A dose-dependent tug of war involving the NPM1 leukaemic mutant, nucleophosmin, and ARF

Abstract: In acute myeloid leukaemia (AML), nucleophosmin-1 (NPM1) mutations create a nuclear export signal (NES) motif and disrupt tryptophans at NPM1 C-terminus, leading to nucleophosmin accumulation in leukaemic cell cytoplasm. We investigated how nucleophosmin NES motifs (two physiological and one created by the mutation) regulate traffic and interaction of mutated NPM1, NPM1wt and p14 ARF . Nucleophosmin export into cytoplasm was maximum when the protein contained all three NES motifs, as naturally occurs in NPM1-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 38 publications
3
54
0
Order By: Relevance
“…On the other hand, in the presence of excess of mutant NPM1, all NPM1wt protein was pulled out of the nucleoli into nucleoplasm and cytoplasm, 27 as seen in some patients with NPM1-mutated AML. On the contrary, excess doses of NPM1wt relocated NPM1 leukaemic mutant from cytoplasm to the nucleoli of transfected cells, 27 a pattern never observed in NPM1-mutated AML patients in whom the mutant was always cytoplasmic restricted. 81 This evidence points at a dose-dependent relationship between wild-type and mutated NPM1 proteins, and supports the view that NPM1 leukaemic mutants are 'born to be exported'.…”
Section: Delocalization Of Npm1wtmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, in the presence of excess of mutant NPM1, all NPM1wt protein was pulled out of the nucleoli into nucleoplasm and cytoplasm, 27 as seen in some patients with NPM1-mutated AML. On the contrary, excess doses of NPM1wt relocated NPM1 leukaemic mutant from cytoplasm to the nucleoli of transfected cells, 27 a pattern never observed in NPM1-mutated AML patients in whom the mutant was always cytoplasmic restricted. 81 This evidence points at a dose-dependent relationship between wild-type and mutated NPM1 proteins, and supports the view that NPM1 leukaemic mutants are 'born to be exported'.…”
Section: Delocalization Of Npm1wtmentioning
confidence: 99%
“…4,58 Core amino acids in the two physiological aminoterminal NES motifs seem to play a major role in mediating NPM1 homo-and hetero-dimerization, by dictating in a 'dosedependent tug of war' fashion the subcellular distribution of wild-type and mutated NPM1 proteins. 27 In fact, transfected cells showed that, when NPM1wt and mutant proteins were expressed at equimolar doses, a fraction of NPM1wt was consistently retained in the nucleoli (as is most often observed in AML samples). On the other hand, in the presence of excess of mutant NPM1, all NPM1wt protein was pulled out of the nucleoli into nucleoplasm and cytoplasm, 27 as seen in some patients with NPM1-mutated AML.…”
Section: Delocalization Of Npm1wtmentioning
confidence: 99%
See 3 more Smart Citations